The Evolution of U.S. Health Care Delivery Policy - Kulesher, Robert R. (My University, 2012)
Laupus Library History Collections & the Department of Bioethics & Interdisciplinary Studies sponsor the History of Medicine Presentations as an educational service for the East Carolina University community. The Library hopes that the speakers and topics selected will promote a greater understanding of the historical and philosophical underpinnings of today's health care disciplines.
Keywords: Medical History Interest Group; MHIG; History of Medicine; Hospitals--history; Hospitals, Private--history; Hospitals, Public--history; Almshouses--history; Health Care Economics and Organizations--history; Blue Cross Blue Shield Insurance Plans--history; Medical Assistance--history; Delivery of Health Care--history; Health Insurance Portability and Accountability Act--history; Patient Protection and Affordable Care Act--history